2018
DOI: 10.3389/fbioe.2018.00099
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Contacting Biomaterials: In Vitro Evaluation of the Hemocompatibility

Abstract: Hemocompatibility of blood-contacting biomaterials is one of the most important criteria for their successful in vivo applicability. Thus, extensive in vitro analyses according to ISO 10993-4 are required prior to clinical applications. In this review, we summarize essential aspects regarding the evaluation of the hemocompatibility of biomaterials and the required in vitro analyses for determining the blood compatibility. Static, agitated, or shear flow models are used to perform hemocompatibility studies. Bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
323
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(342 citation statements)
references
References 111 publications
9
323
2
8
Order By: Relevance
“…Hemolytic activities for LATIS, PGA sutures, and silk sutures were 0.44%, 0.69%, and 0.60%, respectively, compared to fully hemolyzed positive control ( Figure B). Conventionally, blood‐contacting materials which result in less than 2% hemolysis are considered as nonhemolytic . In addition, exposure of LATIS and commercially available PGA and silk sutures to NIH 3T3 and BJ‐5Ta cell lines did not result in significant loss of cell viability at different time intervals (24, 48, and 72 h; Figure C).…”
Section: Resultsmentioning
confidence: 97%
“…Hemolytic activities for LATIS, PGA sutures, and silk sutures were 0.44%, 0.69%, and 0.60%, respectively, compared to fully hemolyzed positive control ( Figure B). Conventionally, blood‐contacting materials which result in less than 2% hemolysis are considered as nonhemolytic . In addition, exposure of LATIS and commercially available PGA and silk sutures to NIH 3T3 and BJ‐5Ta cell lines did not result in significant loss of cell viability at different time intervals (24, 48, and 72 h; Figure C).…”
Section: Resultsmentioning
confidence: 97%
“…Hemocompatibility is one of the major criteria for clinical success in blood-contacting biomaterials [16]. There are many haematological analysis models for analysing the haemocompatibility of biomaterials [20]. In this study, anticoagulated buffy coats with EDTA were used to find the mechanisms of the complement cascade on surface modified Ti coins.…”
Section: Discussionmentioning
confidence: 99%
“…This may reveal one of the weaknesses of this study, e.g., the detection and measurements of biomarkers. Weber et al suggested that these components could be bound to the surfaces [20] and it could be an indirect cause to the lack of differences for C3a and C5a on the various surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of nonadherent cells (retention and consumption), their degree of activation as well as the formation of micro‐thrombi and platelet derived microparticles are classically determined . Expression of activation markers on the platelet membrane (e.g., P‐Selectin) and the release of the soluble agonists from granules and lysosomes (e.g., sP‐Selectin, Platelet Factor 4 and β‐thromboglobulin) indicate their degree of activation and can be studied via flow cytometry and ELISA . In many cases, dynamic in vitro test systems are applied, which allow repeated interactions between the circulating blood cells and the material surface (see section In vitro test systems).…”
Section: Characterization Of the Blood–materials Interactionsmentioning
confidence: 99%